(3caGjI GdCNjGQ aj Md ZGjI GdGNJUGQs - (3GdMUfj, Jbj GdOjf, CHh HcQ Hf eMeO Hf Hf YHO GdeDef, J (B829 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdehLhOGJ ef XdeI GdYOe HfhQ GdEjLGOs
(3BNQgG (B:s
(3hdh NQL ddWdH MGVQG cGf Ch ZGdHG agd jLH GdETgGO Efg Ydi GdWdH GdUMjM aj GdQGaYj hGdQhVI Cfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 69s
(3eYLe GdeDdajf (B1 / 445s
(3cTa GdXfhf (B2 / 1189s
(3TPQGJ GdPgH (B7 / 188s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs